The behavior of the Perbaungan railway subgrade - Aazokhi Waruwu; Muhammad Arfan; Tubel Oktor Waruwu (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2022)
Railway subgrade is a layer consisting of soil material which can be in the form of natural soil, repaired material, and in the form of embankment of selected soil material that meets the specifications. The subgrade that meets the requirements is soil with a minimum CBR value of 8% with a minimum thickness of 30 cm. This study aims to analyze and evaluate the CBR value of the railway subgrade. Subgrade analysis was carried out on the improvement of the railway - replacement of concrete pads and rails R.25/33/42 to R.54 concrete pads from km 39 + 100 to km 40 + 200 along 1100 m in Perbaungan North Sumatra. The structure of the soil layer that is analyzed is the structure of the subsoil in the form of subgrade. The CBR value of the subgrade in the form of soil is determined based on the results of the analysis of the DCP data. The CBR value is evaluated based on the provisions that apply to the railway subgrade. The behavior of the railway subgrade can be seen from the CBR value of the original subgrade. Based on the results of the analysis, it was found that the behavior of the railway subgrade was quite diverse and it was found that only 39% met the requirements for the rail subgrade. Handling carried out in the field to improve the behavior of the subgrade is by using a backfill system made of good material with a density and CBR value that meets the requirements for railways.